Environmental concentrations of prednisolone alter visually mediated responses during early life stages of zebrafish (Danio rerio). (November 2016) - McNeil, Paul L.; Nebot, Carolina; Cepeda, Alberto; Sloman, Katherine A.
Abstract: The development of the eye in vertebrates is dependent upon glucocorticoid signalling, however, specific components of the eye are sensitive to synthetic glucocorticoids. The presence of synthetic glucocorticoids within the aquatic environment may therefore have important consequences for fish, which are heavily reliant upon vision for mediating several key behaviours. The potential ethological impact of synthetic glucocorticoid oculotoxicity however has yet to be studied. Physiological and behavioural responses which are dependent upon vision were selected to investigate the possible toxicity of prednisolone, a commonly occurring synthetic glucocorticoid within the environment, during early life stages of zebrafish. Although exposure to prednisolone did not alter the morphology of the external eye, aggregation of melanin within the skin in response to increasing light levels was impeded and embryos exposed to prednisolone (10 μg/l) maintained a darkened phenotype. Exposure to prednisolone also increased the preference of embryos for a dark environment within a light dark box test in a concentration dependent manner. However the ability of embryos to detect motion appeared unaffected by prednisolone. Therefore, while significant effects were detected in several processes mediated by vision, changes occurred in a manner which suggest that vision was in itself unaffected by prednisolone. Neurological and endocrinological changes during early ontogeny are considered as likely candidates for future investigation. Graphical abstract: Highlights: The oculotoxicity of prednisolone was assessed during zebrafish embryogenesis. Exposure to 10 μg/l resulted in a darkened phenotype during light adaptation. Preference for a dark environment was differentially altered by prednisolone. The detection of motion appeared unaffected by all concentrations of prednisolone. Effects are hypothesised to be mediated via non-visually controlled pathways. Abstract : Exposure to prednisolone alters physiological and behavioural responses to visual stimuli during zebrafish embryogenesis via proposed non-ocular mechanisms.